Salmonella-innovative targeting carrier: Loading with doxorubicin for cancer treatment - Sameh Rabea; Fars K. Alanazi; Abdelkader E. Ashour; Mounir M. Salem-Bekhit; Aymen S. Yassin; Nayera A. Moneib; Abd Elgawad M. Hashem; Nazrul Haq (Elsevier, 2020)
Cell- based targeted delivery is recently gain attention as a promising platform for delivery of anticancer drug in selective and efficient manner. As a new biotechnology platform, bacterial ghosts (BGs) have novel biomedical application as targeted drug delivery system (TDDS). In the current work, Salmonellas' BGs was utilized for the first time as hepatocellular cancer (HCC) in-vitro targeted delivery system. Successful BGs loading and accurate analysis of doxorubicin (DOX) were necessary steps for testing the applicability of DOX loaded BGs in targeting the liver cancer cells. Loading capacity was maximized to reach 27.5 µg/mg (27.5% encapsulation efficiency), by incubation of 10 mg BGs with 1 mg DOX at pH 9 in constant temperature (25 °C) for 10 min. In-vitro release study of DOX loaded BGs showed a sustained release (182 h) obeying Higuchi sustained kinetic release model. The death rate (tested by MTT assay) of HepG2 reached to 64.5% by using of 4 μg/ml, while it was about 51% using the same concentration of the free DOX (P value < 0.0001 One-way ANOVA analysis). The proliferative inhibitory concentration (IC50) of the DOX combined formula was 1.328 µg/ml that was about one third of the IC50 of the free DOX (3.374 μg/ml). Apoptosis analysis (tested by flow-cytometry) showed more accumulation in early apoptosis (8.3%) and late apoptosis/necrosis (91%) by applying 1 μg/ml BGs combined DOX, while 1 μg/ml free DOX showed 33.4% of cells in early apoptosis and 39.3% in late apoptosis/necrosis, (P value˃ 0.05: one-way ANOVA). In conclusion, DOX loaded Salmonellas' BGs are successfully prepared and tested in vivo with promising potential as hepatocellular cancer (HCC) targeted delivery system.